Enhancing the electrochemical performance of TiO2 based material using microwave air plasma treatment with an ECR cavity - Swaroop, Ram; Rani, Pinki; Jamwal, Gaurav; Sabavath, Gopikishan; Kumar, Haldhar; Jewariya, Yogesh (Frontiers in Chemistry, 2022)
For the first time, a facile and effective microwave plasma treatment strategy developed at the central university of Punjab is used to improve electrochemical performance. The plasma cavity of a 2.45 GHz electron cyclotron resonance ion source is used for this purpose. Some shrapnel of TiO2 sample material is prepared, and microwave plasma treatment is performed at microwave frequency 2.45 GHz at 80-watt input power. Microwave plasma treatment is delivered to the respective palette in 30, 60, 80, and 100 seconds intervals. The effect of plasma treatment on other physical and chemical properties has been studied in the context of untreated pellets using various characterization techniques such as UV-visible spectroscopy, FTIR, XRD, and FESEM. The findings revealed that plasma treatment reduced the band gap of the untreated sample by 37% and increased the proportion of disordered, amorphous material in the untreated material. Compared to the untreated sample, the 80-second plasma treatment produced better results, such as the lowest band gap value, high disorder (amorphous), and a reduction in electrochemical charge transfer resistance from 7 to 4Ω. In electrochemical performance studies, the 80-sec plasma-treated sample has a 35% higher capacitance than the untreated sample.